The Influence of social media on developing body image dissatisfaction and eating disorders - Dominika Górska; Kamila Świercz; Magdalena Majcher; Małgorzata Sierpień; Monika Majcher; Agata Pikulicka; Aleksandra Karwańska; Aleksandra Kulbat; Piotr Brzychczy; Mateusz Kulbat (Kazimierz Wielki University, 2023)
INTRODUCTION Social media platforms are commonly used worldwide, affecting every-day living of billions of people. It may impacts both self-esteem and self-evaluation of its users. Formed by social influence, the ideal beauty standards lead to an unhealthy comparison, need of external validation and pursuit of ideal appearance. Induced body image dissatisfaction could be the cause of many different eating disorders or rigorous exercises. Promoted by media, ideal body-image creates unhealthy focus on BMI, weight and shape of one's own body. PURPOSE The aim of this study is to present the current state of knowledge on the impact of social media on evolving dissatisfaction with body image, followed by eating disorders. METHODS For the purposes of writing this article, the available literature was reviewed. The database of medical publications - PubMed database and publicly available books was searched, using keywords such as social media and body image disorders, eating disorders. RESULTS According to reviewed studies, spending more time on following social media intensifies body image disorders among both young women and men, as a result of negative upward comparison of their external appearance. A problematic social media use, passive and focused on image-related platforms, heightens a risk of developing a self-dissatisfaction and body concerns. Disordered eating behaviors are significantly connected to a frequent use of an image-related social media platforms. CONCLUSIONS Maintaining a healthy relationships with peers and parents protects self-esteem of adolescents and lowers the risk of body-image and eating disorders. A greater focus should be put on educating young people about their value, self-assessment and healthy relations.